Peningkatan Keterampilan Menulis Cerita Pendek Dengan Menggunakan Teknik Copy The Master Pada Mahasiswa Pendidikan Bahasa dan Sastra Indonesia STKIP Rokania - Delia Putri (JURNAL PENDIDIKAN ROKANIA, 2017)
This action research is generally aimed at improving the ability to write a short story second semester students study program Language and Literature Education Indonesia STKIP Rokania using the technique of the master copy. Data was collected using a test, questionnaire of students, faculty and student observation sheet, interview, and field notes. Results from the research revealed that the results of the initial test average value of students is 55.38, the first cycle of the average student score was 64.41 and the second cycle of the average value of students' writing is 78.02. Based on the research it was concluded that a copy of the master's technique may improve the ability to write a short story in the second semester students study program Language and Literature Education STKIP Rokania.